Peran Olahraga dalam Meningkatkan Kesehatan Fisik dan Mental pada Wanita Menopause - Khotimah , Khusnul; Tarawan , Vita Murniati; Susanti, Ari Indra; Susiarno , Hadi; Rahim, Agus Hadian; Mose, Johanes C. (Jurnal Porkes, 2025)
Menopause is a natural phase in a woman's life characterized by physical and emotional symptoms and an increased risk of other serious health conditions, so exercise is needed to address these issues. This study aims to explore the types of exercise that are effective for the physical and mental health of menopausal women through a scoping review method. 180 articles were found in total, but 5 of them were duplicated. After screening, 175 articles were successfully screened and finally 8 articles were found that met the inclusion and exclusion criteria. The 8 articles that met the inclusion and exclusion criteria were selected. The results showed that several types of exercise can improve the physical and mental health of menopausal women, such as resistance training, aerobics, SaBang-DolGi walking program, ergonomic exercises, bone joint exercises and terra exercises. These types of exercise can increase muscle strength, reduce depression, improve sleep and cognitive function, improve physical and mental health (including vitality and bone mineral density), and improve overall quality of life. In conclusion, regular exercise has a significant positive impact on improving physical and mental health in menopausal women.